2020
DOI: 10.35691/jbm.0202.0131
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology, Behaviour and Habitat Utilization of Black Drongo (Dicrurus Macrocercus) in Pothwar Plateau, Pakistan

Abstract: Black Drongo is an insectivorous bird native to Pakistan. The present study focused on its feeding preferences, behaviour, ecology and habitat relationships. The study was carried out from first week of December, 2019 to the second week of April, 2020 in the two villages of Rawalpindi named as Daultala (Location-I) and Nata Gujarmall (Location-II). Observations were made by point count method on foot using line transect method. Air (52.27%) was the most commonly used feeding substrate. Aerial feeding mode (52.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Black drongo, one of the key insectivore species that inhabits the agricultural areas and avoids higher elevations (Wiersma et al, 2016). In an earlier study, Black drongo was observed as a competent predator of insects (Kaur and Kler, 2018;Bilal et al, 2020). White wagtail and black drongo did not show a significant reduction in the activity level of brain AChE.…”
Section: Discussionmentioning
confidence: 94%
“…Black drongo, one of the key insectivore species that inhabits the agricultural areas and avoids higher elevations (Wiersma et al, 2016). In an earlier study, Black drongo was observed as a competent predator of insects (Kaur and Kler, 2018;Bilal et al, 2020). White wagtail and black drongo did not show a significant reduction in the activity level of brain AChE.…”
Section: Discussionmentioning
confidence: 94%
“…A study of this species' local distribution, habitat characteristics, population, and behavior is also significant for research. Bilal et al (2020) conducted a feeding ecology, behavior, and habitat utilization of black Drongo in Pothwar Plateau, Pakistan. Similar research can also be carried out at APNP with Drongo species as the objects, particularly Crowbilled Drongo.…”
Section: Resultsmentioning
confidence: 99%